Conductive aerogel and preparation method thereof, conductive agent, positive electrode sheet, secondary battery, electrochemical energy storage device, and electric device

CN122930875APending Publication Date: 2026-10-16PUNA NEW ENERGY TECH (NINGBO) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611174075.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统技术中的石墨烯气凝胶在用于电池领域作为导电剂时,存在以下缺陷:(1)离子扩散受限:均一孔径导致高倍率下浓差极化;(2)电化学腐蚀:碱性环境中石墨烯边缘发生C-OH+OH-→CO32-+H2反应;(3)机械强度差:循环压缩后结构坍塌,回弹率<50%

Benefits of technology

[0039] (1) Ion diffusion optimization: Mesoporous structures provide a higher specific surface area, with a specific surface area >350m². 2 /g, large pores reduce diffusion resistance, achieving a diffusion coefficient increase of at least 5 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930875A_ABST
    Figure CN122930875A_ABST
Patent Text Reader

Abstract

The application discloses a conductive aerogel and a preparation method thereof, a conductive agent, a positive electrode sheet, a secondary battery, an electrochemical energy storage device and an electric equipment. The conductive aerogel comprises a graphene framework and a passivation layer, the graphene framework has a macropore and a mesopore, the pore diameter of the macropore is 400nm-600nm, the pore diameter of the mesopore is 40nm-60nm, and the passivation layer comprises an amorphous Al2O3 layer and a nanocrystalline TiN layer which are sequentially connected to the surface of the graphene framework. The conductive aerogel disclosed by the application can reduce diffusion resistance, improve diffusion coefficient, has double corrosion prevention capacity and strong mechanical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials technology, and in particular to conductive aerogels and their preparation methods, conductive agents, positive electrode sheets, secondary batteries, electrochemical energy storage devices, and electrical equipment. Background Technology

[0002] Graphene aerogel, as a conductive agent, not only inherits the excellent high conductivity and large specific surface area of ​​graphene itself due to its unique three-dimensional porous network structure, but also achieves efficient charge transport capability through continuous conductive pathways and extremely low density. Its cross-linked graphene sheet structure can form a permeable network in composite materials, significantly reducing the interfacial resistance of electrode materials. At the same time, the high porosity provides a fast diffusion channel for electrolyte ions, making it particularly suitable for high power density supercapacitors, batteries, and flexible electronic devices. When graphene aerogel in traditional technology is used as a conductive agent in the field of batteries, it has the following defects: (1) Restricted ion diffusion: uniform pore size leads to concentration polarization at high rates; (2) Electrochemical corrosion: C-OH+OH occurs at the edge of graphene in alkaline environment. - →CO3 2- +H2 reaction; (3) Poor mechanical strength: the structure collapses after cyclic compression, and the rebound rate is <50%. Summary of the Invention

[0003] Therefore, it is necessary to provide a conductive aerogel that can reduce diffusion resistance, increase diffusion coefficient, has dual anti-corrosion capabilities, and strong mechanical stability.

[0004] One embodiment of this application provides a conductive aerogel.

[0005] A conductive aerogel includes a graphene framework and a passivation layer. The graphene framework has macropores and mesopores. The macropores have a pore size of 400 nm to 600 nm, and the mesopores have a pore size of 40 nm to 60 nm. The passivation layer includes an amorphous Al2O3 layer and a nanocrystalline TiN layer sequentially connected to the surface of the graphene framework.

[0006] In some embodiments, the graphene framework includes a plurality of macropores and a plurality of mesopores, wherein the volume percentage of the macropores is greater than or equal to 60%, and the volume percentage of the mesopores is less than or equal to 40%.

[0007] In some embodiments, the thickness of the amorphous Al2O3 layer is 0.8 nm to 1.2 nm.

[0008] In some embodiments, the thickness of the nanocrystalline TiN layer is 0.4 nm to 0.6 nm.

[0009] In some embodiments, the grain size of the nanocrystalline TiN layer is 2nm to 3nm.

[0010] One embodiment of this application provides a method for preparing conductive aerogel.

[0011] A method for preparing a conductive aerogel according to an embodiment of this application includes the following steps:

[0012] A macroporous sacrificial template and a mesoporous inorganic template are mixed, and a graphene oxide dispersion is added to form a mixed material;

[0013] The mixed material is subjected to directional freeze-forming and then dried to obtain a first intermediate.

[0014] Stepwise pyrolysis: The first intermediate is pyrolyzed at a temperature of 400°C to 450°C to obtain the second intermediate;

[0015] The second intermediate is subjected to acid washing to form a graphene framework containing macropores and mesopores, wherein the pore size of the macropores is 400nm~600nm and the pore size of the mesopores is 40nm~60nm.

[0016] Furthermore, a passivation layer comprising sequentially stacked amorphous Al2O3 layers and nanocrystalline TiN layers is prepared on the surface of the graphene framework.

[0017] In some embodiments, the macroporous sacrificial template includes at least one of PMMA microspheres, polystyrene microspheres, melamine-formaldehyde resin microspheres, polyethylene microspheres, and polylactic acid microspheres.

[0018] In some embodiments, the mesoporous inorganic template includes at least one of nano-CaCO3, nano-MgCO3, nano-ZnO, nano-MgO, nano-SiO2, NaCl, and KCl.

[0019] In some embodiments, the mass ratio between the macroporous sacrificial template and the mesoporous inorganic template is 1:(0.2~0.5).

[0020] In some embodiments, the temperature of the directional cryogenic forming process is -35°C to -25°C.

[0021] In some embodiments, the freezing direction of the directional cryogenic forming process is vertically upward.

[0022] In some embodiments, the drying process meets the following conditions: freeze drying at a temperature of -50°C to -60°C for 24 to 48 hours.

[0023] In some embodiments, the amorphous Al2O3 layer and the nanocrystalline TiN layer are prepared on the surface of the graphene framework under the following conditions: the amorphous Al2O3 layer and the nanocrystalline TiN layer are prepared by atomic layer deposition, wherein the amorphous Al2O3 layer is grown for 50 to 60 cycles, with a thickness of 0.016 nm to 0.020 nm per cycle, a TMA pulse time of 0.015 s to 0.020 s, and an H2O pulse time of 0. The nitrogen purging time is 8s~0.020s, the deposition temperature is 180℃~220℃; the nanocrystalline TiN layer is grown for 15~25 cycles, with a thickness of 0.020nm~0.030nm per cycle, a TiCl4 pulse time of 0.05s~0.06s, an NH3 pulse time of 0.10s~0.12s, a nitrogen purging time of 10s~15s, and a deposition temperature of 350℃~400℃.

[0024] In some embodiments, the nanocrystalline TiN layer is prepared under the following conditions: TiCl4 is introduced with a pulse time of 0.05s to 0.06s; NH3 is introduced with a pulse time of 0.1s to 0.12s; the thickness of the nanocrystalline TiN layer is controlled to be 0.4nm to 0.6nm; and the grain size of the nanocrystalline TiN layer is 2nm to 3nm.

[0025] One embodiment of this application provides a positive electrode sheet.

[0026] According to one embodiment of this application, a positive electrode sheet includes a layered oxide active material, a conductive agent, and a binder. The conductive agent is at least one of the conductive aerogels described in any of the above embodiments and conductive aerogels prepared by the preparation methods described in any of the above embodiments.

[0027] In some embodiments, the active substance is NaNi. x Mn y Co z O2, where x+y+z=1, x≥0.5.

[0028] One embodiment of this application provides a secondary battery.

[0029] A secondary battery according to one embodiment of this application includes the positive electrode sheet described in any of the above embodiments;

[0030] In some embodiments, the secondary battery includes a sodium-ion battery.

[0031] In some embodiments, the sodium-ion battery further includes a negative electrode, a separator, and an electrolyte, wherein the electrolyte includes an aqueous electrolyte with a pH of 7 to 14.

[0032] One embodiment of this application provides an electrochemical energy storage device.

[0033] An electrochemical energy storage device according to an embodiment of this application includes at least one of the conductive aerogel described in any of the above embodiments, the conductive aerogel prepared by the preparation method described in any of the above embodiments, and a secondary battery described in any of the above embodiments, wherein the secondary battery is used to store electrical energy.

[0034] One embodiment of this application provides an electrical device.

[0035] An electrical device according to an embodiment of this application includes at least one of the conductive aerogel described in any of the above embodiments, the conductive aerogel prepared by the preparation method described in any of the above embodiments, and a secondary battery described in any of the above embodiments, wherein the secondary battery is used to provide electrical energy.

[0036] The aforementioned conductive aerogel can reduce diffusion resistance, increase the diffusion coefficient, possess dual corrosion resistance, and exhibit strong mechanical stability. In some embodiments, the conductive aerogel material has a conductivity >1000 S / m, a conductivity recovery rate ≥98% after 80% compression, and a structural resilience ≥99%. In some embodiments, when this conductive aerogel material is used as an electrode in a high-load aqueous sodium-ion battery, it can achieve a 10C rate capacity retention rate of 85%.

[0037] In at least some embodiments, the above-mentioned conductive aerogel is prepared by a dual-template method using a macroporous sacrificial template and a mesoporous inorganic template to construct a graphene framework with a gradient pore structure containing macropores and mesopores, wherein the macropores are 400nm~600nm and the mesopores are 40nm~60nm. Then, a double passivation layer composed of Al2O3 and TiN is sequentially coated on the surface of the graphene framework to achieve dual corrosion protection and improve mechanical stability.

[0038] In at least some embodiments, the above-described conductive aerogel has at least the following beneficial effects:

[0039] (1) Ion diffusion optimization: Mesoporous structures provide a higher specific surface area, with a specific surface area >350m². 2 / g, large pores reduce diffusion resistance, achieving a diffusion coefficient increase of at least 5 times.

[0040] (2) Dual corrosion protection: Al2O3 blocks electrolyte penetration, TiN provides conductive passivation, and the point defect density is <10 16 cm -3 Corrosion current density <10 -9 A / cm 2 .

[0041] (3) Mechanical stability: The gradient hole structure disperses stress, and the compression rebound rate is >99%, which effectively improves mechanical strength and mechanical stability. Attached Figure Description

[0042] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0043] To gain a more complete understanding of this application and its beneficial effects, the following description will be provided in conjunction with the accompanying drawings. In the following description, the same reference numerals denote the same parts.

[0044] Figure 1 This is a schematic diagram of the preparation method of conductive aerogel according to an embodiment of this application;

[0045] Figure 2 This is a schematic diagram of the conductive aerogel hierarchical pore structure and double passivation layer of the conductive aerogel prepared in Example 1.

[0046] Figure 3 See the comparison chart of relevant performance parameters between the embodiments and comparative examples of this application. Figure 3 As shown. Detailed Implementation

[0047] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.

[0048] In the description of this application, "several" means one or more, "multiple" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.

[0049] In this document, "optionally," "optionally," and "optional" mean that something is optional, that is, it is selected from either "with" or "without." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "option" is independent. In this application, descriptions such as "optionally contains" and "optionally includes" indicate "contains or does not contain."

[0050] In this application, unless otherwise stated, the sum of the parts of each component in the composition may be 100 parts by weight. Unless otherwise specified, the percentages (including weight percentages) in this application are based on the total weight of the composition, and "wt%" in this document means mass percentage.

[0051] In this document, unless otherwise stated, the reaction steps may be performed in the order described herein or not. For example, other steps may be included between reaction steps, and the order of reaction steps may be appropriately interchanged. This is something that those skilled in the art can determine based on conventional knowledge and experience. Preferably, the reaction methods described herein are performed sequentially.

[0052] In this application, when numerical intervals (i.e., numerical ranges) are mentioned, unless otherwise specified, the distribution of selectable numerical values ​​within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0054] One embodiment of this application provides a conductive aerogel to address the following defects of traditional graphene aerogels when used as conductive agents in the battery field: (1) limited ion diffusion: uniform pore size leads to concentration polarization at high rates; (2) electrochemical corrosion: C-OH+OH occurs at the edge of graphene in an alkaline environment. - →CO3 2- +H2 reaction; (3) Poor mechanical strength: the structure collapses after cyclic compression, and the rebound rate is <50%. The following will explain the conductive aerogel with reference to the attached figures.

[0055] The conductive aerogel provided in one embodiment of this application is exemplary; please refer to [link to relevant documentation]. Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of a conductive aerogel provided in one embodiment of this application. The conductive aerogel of this application can be used to prepare conductive agents, battery electrodes, and batteries.

[0056] To illustrate the structure of conductive aerogel more clearly, the following description of conductive aerogel will be provided in conjunction with the accompanying drawings.

[0057] For example, please refer to Figure 1 As shown, a conductive aerogel includes a graphene framework and a passivation layer. The graphene framework has macropores and mesopores. The macropores have a pore size of 400 nm to 600 nm, and the mesopores have a pore size of 40 nm to 60 nm. The passivation layer includes an amorphous Al₂O₃ layer and a nanocrystalline TiN layer sequentially connected to the surface of the graphene framework. For example, the pore size of the macropores includes, but is not limited to, 400 nm, 420 nm, 440 nm, 460 nm, 480 nm, 500 nm, 520 nm, 540 nm, 560 nm, 580 nm, 600 nm, or any range between the aforementioned. For example, the pore size of mesopores includes, but is not limited to: 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, or any range between the two aforementioned.

[0058] The aforementioned conductive aerogel can reduce diffusion resistance, increase the diffusion coefficient, possess dual corrosion resistance, and exhibit strong mechanical stability. In some embodiments, the conductive aerogel material has a conductivity >1000 S / m, a conductivity recovery rate ≥98% after 80% compression, and a structural resilience ≥99%. In some embodiments, when this conductive aerogel material is used as an electrode in a high-load aqueous sodium-ion battery, it can achieve a 10C rate capacity retention rate of 85%.

[0059] In some embodiments, the graphene framework includes multiple graphene sheets that form a 3D network, and the number of graphene sheets is 3 to 5.

[0060] In some embodiments, the graphene framework includes multiple macropores and multiple mesopores, wherein the volume percentage of macropores is greater than or equal to 60%, and the volume percentage of mesopores is less than or equal to 40%.

[0061] In some embodiments, the volume percentage of macropores is greater than or equal to 60% and less than or equal to 80%, and the volume percentage of mesopores is greater than or equal to 20% and less than or equal to 40%. For example, the volume percentage of macropores includes, but is not limited to: 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, or any range between any two of the foregoing. For example, the volume percentage of mesopores includes, but is not limited to: 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or any range between any two of the foregoing.

[0062] In some embodiments, the thickness of the amorphous Al2O3 layer is 0.8 nm to 1.2 nm. For example, the thickness of the amorphous Al2O3 layer may include, but is not limited to, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, or any range between the two aforementioned.

[0063] In some embodiments, the thickness of the nanocrystalline TiN layer is 0.4 nm to 0.6 nm. For example, the thickness of the nanocrystalline TiN layer includes, but is not limited to, 0.4 nm, 0.45 nm, 0.5 nm, 0.55 nm, 0.6 nm, or any range between the two aforementioned.

[0064] In some embodiments, the grain size of the nanocrystalline TiN layer is 2 nm to 3 nm. For example, the grain size of the nanocrystalline TiN layer includes, but is not limited to: 2 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3 nm, or any range between the foregoing.

[0065] One embodiment of this application provides a method for preparing conductive aerogel.

[0066] A method for preparing a conductive aerogel according to an embodiment of this application includes the following steps:

[0067] S10. Mix the macroporous sacrificial template with the mesoporous inorganic template, and add the graphene oxide dispersion to form a mixed material.

[0068] S20. The mixed material is subjected to directional freeze molding and then dried to obtain the first intermediate.

[0069] S30. The first intermediate is pyrolyzed at a temperature of 400°C to 450°C to obtain the second intermediate. For example, the temperature values ​​for the first pyrolysis treatment include, but are not limited to: 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, or any range between the two aforementioned. For example, the temperature values ​​for the second pyrolysis treatment include, but are not limited to: 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, or any range between the two aforementioned.

[0070] S40. The second intermediate is subjected to acid washing to remove CaO and form a graphene framework containing macropores and mesopores, wherein the pore size of the macropores is 400nm~600nm and the pore size of the mesopores is 40nm~60nm.

[0071] S50, a passivation layer comprising sequentially stacked amorphous Al2O3 layers and nanocrystalline TiN layers is prepared on the surface of a graphene framework.

[0072] In at least some embodiments, the above-mentioned conductive aerogel is prepared by a dual-template method using a macroporous sacrificial template and a mesoporous inorganic template to construct a graphene framework with a gradient pore structure containing macropores and mesopores, wherein the macropores are 400nm~600nm and the mesopores are 40nm~60nm. Then, a double passivation layer composed of Al2O3 and TiN is sequentially coated on the surface of the graphene framework to achieve dual corrosion protection and improve mechanical stability.

[0073] In some embodiments, the macroporous sacrificial template includes at least one of PMMA microspheres, polystyrene microspheres, melamine-formaldehyde resin microspheres, polyethylene microspheres, and polylactic acid microspheres.

[0074] In some embodiments, the mesoporous inorganic template includes at least one of nano-CaCO3, nano-MgCO3, nano-ZnO, nano-MgO, nano-SiO2, NaCl, and KCl. The macroporous sacrificial template and the mesoporous inorganic template must be compatible with the graphene oxide dispersion, be stably dispersed during directional freezing, and be subsequently removable to form macropores of 400 nm to 600 nm and mesopores of 40 nm to 60 nm.

[0075] In some embodiments, the mass ratio between the macroporous sacrificial template and the mesoporous inorganic template is 1:(0.2~0.5). For example, the mass ratio between the macroporous sacrificial template and the mesoporous inorganic template may be, but is not limited to, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or any range between the foregoing.

[0076] In some embodiments, the temperature for directional freeze forming is -35°C to -25°C. For example, the temperature for directional freeze forming includes, but is not limited to: -35°C, -34°C, -33°C, -32°C, -31°C, -30°C, -29°C, -28°C, -27°C, -26°C, -25°C, or any range between the foregoing.

[0077] In some embodiments, the freezing direction of the directional cryogenic forming process is vertically upward.

[0078] In some embodiments, the drying process satisfies the following conditions: freeze-drying at a temperature of -50°C to -60°C for 24 to 48 hours. For example, the temperature values ​​for the freeze-drying process include, but are not limited to: -50°C, -51°C, -52°C, -53°C, -54°C, -55°C, -56°C, -57°C, -58°C, -59°C, -60°C, or any range between the two aforementioned; the freeze-drying time values ​​include, but are not limited to: 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours, 48 ​​hours, or any range between the two aforementioned.

[0079] In some embodiments, the amorphous Al2O3 layer and the nanocrystalline TiN layer are prepared on the surface of the graphene framework under the following conditions: the amorphous Al2O3 layer and the nanocrystalline TiN layer are prepared by atomic layer deposition, wherein the amorphous Al2O3 layer is prepared by 50 to 60 cycles, with a growth thickness of 0.016 nm to 0.020 nm per cycle, a TMA pulse time of 0.015 s to 0.020 s, an H2O pulse time of 0.015 s to 0.020 s, a nitrogen purging time of 8 s to 12 s, and a deposition temperature of 180 °C to 220 °C. The nanocrystalline TiN layer is prepared by 15 to 25 cycles, with a growth thickness of 0.020 nm to 0.030 nm per cycle, a TiCl4 pulse time of 0.05 s to 0.06 s, an NH3 pulse time of 0.10 s to 0.12 s, a nitrogen purging time of 10 s to 15 s, and a deposition temperature of 350 °C to 400 °C. For example, the number of deposition cycles for amorphous Al2O3 layers includes, but is not limited to: 50 cycles, 51 cycles, 52 cycles, 53 cycles, 54 cycles, 55 cycles, 56 cycles, 57 cycles, 58 cycles, 59 cycles, 60 cycles, or any range between the two aforementioned; the number of deposition cycles for nanocrystalline TiN layers includes, but is not limited to: 15 cycles, 16 cycles, 17 cycles, 18 cycles, 19 cycles, 20 cycles, 21 cycles, 22 cycles, 23 cycles, 24 cycles, 25 cycles, or any range between the two aforementioned.

[0080] In some embodiments, the nanocrystalline TiN layer is prepared under the following conditions: TiCl4 is introduced with a pulse duration of 0.05 s to 0.06 s, the thickness of the nanocrystalline TiN layer is controlled to be 0.4 nm to 0.6 nm, and the grain size of the nanocrystalline TiN layer is 2 nm to 3 nm. For example, the pulse duration may include, but is not limited to, 0.05 s, 0.051 s, 0.052 s, 0.053 s, 0.054 s, 0.055 s, 0.056 s, 0.057 s, 0.058 s, 0.059 s, 0.06 s, or any range between the two. NH3 is introduced with a pulse duration of 0.1 s to 0.12 s, for example, the pulse duration may include, but is not limited to, 0.1 s, 0.11 s, 0.12 s, or any range between the two.

[0081] In some embodiments, the pyrolysis treatment includes: performing a first pyrolysis treatment on the first intermediate at a temperature of 400°C to 450°C to remove PMMA, and then performing a second pyrolysis treatment at a temperature of 800°C to 900°C to convert CaCO3 into CaO, thereby obtaining a second intermediate.

[0082] One embodiment of this application provides a positive electrode sheet.

[0083] A positive electrode sheet according to one embodiment of this application includes a layered oxide active material, a conductive agent, and a binder. The conductive agent is at least one of the conductive aerogels in any of the above embodiments and conductive aerogels prepared by the preparation methods in any of the above embodiments.

[0084] In some embodiments, the active material is NaNi. x Mn y Co z O2, where x+y+z=1, x≥0.5.

[0085] One embodiment of this application provides a secondary battery.

[0086] A secondary battery according to one embodiment of this application includes the positive electrode sheet of any of the above embodiments.

[0087] In some of these implementations, the secondary battery includes a sodium-ion battery.

[0088] In some embodiments, the sodium-ion battery further includes a negative electrode, a separator, and an electrolyte, wherein the electrolyte comprises an aqueous electrolyte with a pH value of 7 to 14. For example, the pH value of the aqueous electrolyte includes, but is not limited to: 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10, 10.2, 10.4, 10.6, 10.8, 11, 11.2, 11.4, 11.6, 11.8, 12, 12.2, 12.4, 12.6, 12.8, 13, 13.2, 13.4, 13.6, 13.8, 14, or any range between the foregoing.

[0089] In some embodiments, the aqueous electrolyte includes aqueous solutions of sodium salts such as Na2SO4, NaNO3, NaClO4, and CH3COONa, with a pH range of 7 to 14.

[0090] In some embodiments, the aqueous electrolyte may also include an electrolyte formed by dissolving 1 mol / L NaPF6 in a carbonate solvent system such as EC / DMC / DEC.

[0091] In some embodiments, after the positive electrode sheet is used to prepare a sodium-ion battery, the porosity of the positive electrode sheet decreases by ≤5% after 500 cycles at a 10C rate.

[0092] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode plates and electrolyte.

[0093] One embodiment of this application provides an electrochemical energy storage device.

[0094] An electrochemical energy storage device according to an embodiment of this application includes at least one of the conductive aerogel in any of the above embodiments, the conductive aerogel prepared by the preparation method in any of the above embodiments, and a secondary battery in any of the above embodiments, wherein the secondary battery is used to store electrical energy.

[0095] In some embodiments, the electrochemical energy storage device may include an outer packaging. This outer packaging can be used to encapsulate the aforementioned electrode plates and electrolyte.

[0096] One embodiment of this application provides an electrical device.

[0097] An electrical device according to one embodiment of this application includes at least one of the conductive aerogel in any of the above embodiments, the conductive aerogel prepared by the preparation method in any of the above embodiments, and a secondary battery in any of the above embodiments, wherein the secondary battery is used to provide electrical energy.

[0098] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode plates and electrolyte.

[0099] In some embodiments, the outer packaging of the secondary battery can be a rigid shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic; further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0100] Secondary batteries can be used as the power source for an electrical device or as the energy storage unit of that device. Electrical devices can include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be, for example, mobile phones and laptops; electric vehicles can be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0101] Example 1

[0102] This embodiment provides a conductive aerogel.

[0103] The method for preparing the conductive aerogel in this embodiment includes the following steps:

[0104] S100. PMMA microspheres and nano-CaCO3 are mixed at a mass ratio of 1:0.35, and graphene oxide dispersion is added to form a mixed material.

[0105] S200. The mixed material is subjected to directional freeze-drying treatment with the freezing direction vertically upward at a temperature of -30℃, and then vacuum freeze-drying treatment at a temperature of -55℃ to obtain the first intermediate.

[0106] S300, Step pyrolysis: The first intermediate is subjected to a first pyrolysis treatment at 420°C to remove PMMA, and then subjected to a second pyrolysis treatment at 850°C to convert CaCO3 into CaO, to obtain the second intermediate.

[0107] S400, the second intermediate is acid-washed to remove CaO and form a graphene framework containing macropores and mesopores; wherein the volume ratio of macropores is 60% and the volume ratio of mesopores is 40%.

[0108] S500 uses atomic layer deposition to prepare amorphous Al2O3 layers and nanocrystalline TiN layers on the surface of a graphene framework.

[0109] The precursor for preparing the amorphous Al2O3 layer was TMA / H2O. The amorphous Al2O3 layer was prepared by a 55-cycle process and the thickness of the amorphous Al2O3 layer was 1 nm.

[0110] The precursor for preparing the nanocrystalline TiN layer was TiCl4 / NH3, where the TiCl4 pulse duration was 0.055 s and the NH3 pulse duration was 0.1 s. The nanocrystalline TiN layer was prepared by 20 cycles, and the thickness of the nanocrystalline TiN layer was 0.5 nm.

[0111] See Figure 2 As shown, Figure 2 This is a schematic diagram of the conductive aerogel layered pore structure and double passivation layer prepared in Example 1. The conductive aerogel prepared in this example is applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet includes a layered oxide active material, a conductive agent, and a binder. The active material is Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent is the conductive aerogel prepared in this embodiment, with a content of 3 wt%; the binder is PVDF, with a content of 2 wt%.

[0112] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0113] Example 2

[0114] This embodiment provides a conductive aerogel.

[0115] The method for preparing the conductive aerogel in this embodiment includes the following steps:

[0116] S100. PMMA microspheres and nano-CaCO3 are mixed at a mass ratio of 1:0.2, and graphene oxide dispersion is added to form a mixed material.

[0117] S200. The mixed material is subjected to directional freeze-drying treatment with the freezing direction vertically upward at a temperature of -35°C, and then vacuum freeze-drying treatment at a temperature of -50°C to obtain the first intermediate.

[0118] S300, Step pyrolysis: The first intermediate is subjected to a first pyrolysis treatment at 400°C to remove PMMA, and then subjected to a second pyrolysis treatment at 800°C to convert CaCO3 into CaO, to obtain the second intermediate.

[0119] S400, the second intermediate is acid-washed to remove CaO and form a graphene framework containing macropores and mesopores; wherein the volume ratio of macropores is 70% and the volume ratio of mesopores is 30%.

[0120] S500 uses atomic layer deposition to prepare amorphous Al2O3 layers and nanocrystalline TiN layers on the surface of a graphene framework.

[0121] The precursor for preparing the amorphous Al2O3 layer was TMA / H2O. The amorphous Al2O3 layer was prepared by 50 cycles and the thickness of the amorphous Al2O3 layer was 0.8 nm.

[0122] The precursor for preparing the nanocrystalline TiN layer was TiCl4 / NH3, where the TiCl4 pulse duration was 0.05 s and the NH3 pulse duration was 0.1 s. The nanocrystalline TiN layer was prepared by 15 cycles, and the thickness of the nanocrystalline TiN layer was 0.4 nm.

[0123] The conductive aerogel prepared in this embodiment is applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet includes a layered oxide active material, a conductive agent, and a binder. The active material is Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent is the conductive aerogel prepared in this embodiment, with a content of 3 wt%; the binder is PVDF, with a content of 2 wt%.

[0124] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0125] Example 3

[0126] This embodiment provides a conductive aerogel.

[0127] The method for preparing the conductive aerogel in this embodiment includes the following steps:

[0128] S100. PMMA microspheres and nano-CaCO3 are mixed at a mass ratio of 1:0.5, and graphene oxide dispersion is added to form a mixed material.

[0129] S200. The mixed material is subjected to directional freeze-drying treatment with the freezing direction vertically upward at a temperature of -25°C, and then vacuum freeze-drying treatment at a temperature of -60°C to obtain the first intermediate.

[0130] S300, Step pyrolysis: The first intermediate is subjected to a first pyrolysis treatment at 450°C to remove PMMA, and then subjected to a second pyrolysis treatment at 900°C to convert CaCO3 into CaO, thus obtaining the second intermediate.

[0131] S400, the second intermediate is acid-washed to remove CaO and form a graphene framework containing macropores and mesopores; wherein the volume ratio of macropores is 65% and the volume ratio of mesopores is 35%.

[0132] S500 uses atomic layer deposition to prepare amorphous Al2O3 layers and nanocrystalline TiN layers on the surface of a graphene framework.

[0133] The precursor for preparing the amorphous Al2O3 layer was TMA / H2O. The amorphous Al2O3 layer was prepared by 60 cycles and the thickness of the amorphous Al2O3 layer was 1.2 nm.

[0134] The precursor for preparing the nanocrystalline TiN layer was TiCl4 / NH3, where the TiCl4 pulse duration was 0.06 s and the NH3 pulse duration was 0.12 s. The nanocrystalline TiN layer was prepared by 25 cycles, and the thickness of the nanocrystalline TiN layer was 0.6 nm.

[0135] The conductive aerogel prepared in this embodiment is applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet includes a layered oxide active material, a conductive agent, and a binder. The active material is Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent is the conductive aerogel prepared in this embodiment, with a content of 3 wt%; the binder is PVDF, with a content of 2 wt%.

[0136] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0137] Comparative Example 1

[0138] This comparative example provides a positive electrode sheet.

[0139] The positive electrode sheet comprises a layered oxide active material, a conductive agent, and a binder. The active material is Na3V2(PO4)3 with a loading of 40 mg / cm³.2 The conductive agent is acetylene black, which is produced using traditional technology, and the content of acetylene black is 3 wt%.

[0140] Comparative Example 2

[0141] This comparative example provides a conductive aerogel.

[0142] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 1. The difference is that in this comparative example, the mass ratio of PMMA microspheres to nano-CaCO3 is 1:0.1, that is, the amount of nano-CaCO3 is relatively small.

[0143] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0144] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0145] Comparative Example 3

[0146] This comparative example provides a conductive aerogel.

[0147] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 1. The difference is that in this comparative example, the mass ratio of PMMA microspheres to nano-CaCO3 is 1:0.7, that is, nano-CaCO3 is more abundant.

[0148] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0149] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0150] Comparative Example 4

[0151] This comparative example provides a conductive aerogel.

[0152] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 2. The difference is that the temperature of the directional freeze-forming treatment in this comparative example is -15℃, that is, the temperature of the freeze-forming treatment is relatively high.

[0153] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm2. The conductive agent was the conductive aerogel prepared in this comparative example with a content of 3 wt%. The binder was PVDF with a content of 2 wt%.

[0154] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0155] Comparative Example 5

[0156] This comparative example provides a conductive aerogel.

[0157] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 2, except that in this comparative example, the freezing direction is unidirectional freezing in the horizontal direction.

[0158] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0159] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0160] Comparative Example 6

[0161] This comparative example provides a conductive aerogel.

[0162] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 3. The difference is that in this comparative example, step pyrolysis was not performed, but the temperature of the first pyrolysis treatment and the second pyrolysis treatment was 450°C.

[0163] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0164] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0165] Comparative Example 7

[0166] This comparative example provides a conductive aerogel.

[0167] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 3. The difference is that step S400 is omitted in this comparative example, that is, the second intermediate is not acid washed.

[0168] S500 uses atomic layer deposition to prepare amorphous Al2O3 layers and nanocrystalline TiN layers on the surface of a graphene framework.

[0169] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0170] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0171] Comparative Example 8

[0172] This comparative example provides a conductive aerogel.

[0173] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 3. The difference is that step S500 is omitted in this comparative example, that is, the atomic layer deposition method is not used to prepare the amorphous Al2O3 layer and the nanocrystalline TiN layer on the surface of the graphene framework.

[0174] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0175] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0176] Comparative Example 9

[0177] This comparative example provides a conductive aerogel.

[0178] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 3. The difference is that in this comparative example, only the atomic layer deposition method is used to prepare an amorphous Al2O3 layer on the surface of the graphene framework in step S500, that is, it does not contain a nanocrystalline TiN layer.

[0179] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0180] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1.

[0181] Comparative Example 10

[0182] This comparative example provides a conductive aerogel.

[0183] The preparation method of the conductive aerogel in this comparative example is basically the same as that in Example 3. The difference is that in this comparative example, only the atomic layer deposition method is used to prepare a nanocrystalline TiN layer on the surface of the graphene framework in step S500, that is, it does not contain an amorphous Al2O3 layer.

[0184] The conductive aerogel prepared in this comparative example was applied to an electrode to prepare a positive electrode sheet. The positive electrode sheet included a layered oxide active material, a conductive agent, and a binder. The active material was Na3V2(PO4)3 with a loading of 40 mg / cm³. 2 The conductive agent was the conductive aerogel prepared in this comparative example, with a content of 3 wt%; the binder was PVDF, with a content of 2 wt%.

[0185] Performance testing: In 1M Na2SO4 electrolyte, at a rate of 0.5C, the comparison results are shown in Table 1. Additionally, a comparison chart of relevant performance parameters between the examples and comparative examples can be found in [link to example chart]. Figure 3 As shown.

[0186] Table 1

[0187]

[0188] The electrode preparation and testing steps in this application are as follows:

[0189] 1. Preparation of positive electrode slurry: Na3V2(PO4)3 was used as the active material, and the active material: conductive agent: PVDF was prepared in a mass ratio of 95:3:2. NMP was added and stirred to form a uniform slurry. The conductive agent in Examples 1-3 and Comparative Examples 2-10 was the corresponding conductive aerogel, and the conductive agent in Comparative Example 1 was acetylene black.

[0190] 2. Electrode preparation: The slurry is coated onto the surface of the aluminum foil current collector, pre-dried at 80℃ for 30 min, then vacuum-dried at 120℃ for 12 h, rolled, and cut into electrode sheets, with the active material loading controlled at 40 mg / cm³. 2 .

[0191] 3. Battery assembly: Assemble button or pouch cells using the obtained positive electrode, glass fiber separator and sodium metal / hard carbon negative electrode. Use 1 mol / L Na2SO4 aqueous electrolyte with pH 7-8.

[0192] 4. Rate performance test: After standing at 25℃ for 6 hours, activate at 0.5C for 2 cycles, and then perform constant current charge and discharge at 0.5C and 10C respectively. Record the percentage of 10C discharge capacity relative to 0.5C discharge capacity as the 10C capacity retention rate.

[0193] 5. Areal Capacity Calculation: The areal capacity is calculated by dividing the 0.5C discharge capacity by the positive electrode area, with units of mAh / cm². 2 .

[0194] 6. Compression stability test: The conductive aerogel sample was subjected to 100 cycles of compression at 80% compression deformation. The resistance before and after the cycle was tested using the four-probe method. The increase in resistance after 100 compressions was calculated as (resistance after cycle - resistance before cycle) / resistance before cycle × 100%.

[0195] 7. Corrosion stability test: The conductive aerogel was placed in a 1 mol / L Na2SO4 aqueous electrolyte for potentiodynamic polarization test. The scan rate was 1 mV / s, and the corrosion current density was recorded to evaluate the corrosion resistance of the double passivation layer.

[0196] In summary, the above-mentioned conductive aerogel has at least the following beneficial effects:

[0197] (1) Ion diffusion optimization: Mesoporous structures provide a higher specific surface area, with a specific surface area >350m². 2 / g, large pores reduce diffusion resistance, achieving a diffusion coefficient increase of at least 5 times.

[0198] (2) Dual corrosion protection: Al2O3 blocks electrolyte penetration, TiN provides conductive passivation, and the point defect density is <10 16 cm -3 Corrosion current density <10 -9 A / cm 2 .

[0199] (3) Mechanical stability: The gradient hole structure disperses stress, and the compression rebound rate is >99%, which effectively improves mechanical strength and mechanical stability.

[0200] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.

[0201] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0202] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.

Claims

1. A conductive aerogel, characterized in that, The invention includes a graphene framework and a passivation layer. The graphene framework has macropores and mesopores. The macropores have a diameter of 400 nm to 600 nm, and the mesopores have a diameter of 40 nm to 60 nm. The passivation layer includes an amorphous Al2O3 layer and a nanocrystalline TiN layer sequentially connected to the surface of the graphene framework.

2. The conductive aerogel according to claim 1, characterized in that, The graphene framework includes a plurality of macropores and a plurality of mesopores, wherein the volume percentage of the macropores is greater than or equal to 60%, and the volume percentage of the mesopores is less than or equal to 40%.

3. The conductive aerogel according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: (1) The thickness of the amorphous Al2O3 layer is 0.8 nm to 1.2 nm; (2) The thickness of the nanocrystalline TiN layer is 0.4 nm to 0.6 nm; (3) The grain size of the nanocrystalline TiN layer is 2nm~3nm.

4. A method for preparing a conductive aerogel, characterized in that, Includes the following steps: A macroporous sacrificial template and a mesoporous inorganic template are mixed, and a graphene oxide dispersion is added to form a mixed material; The mixed material is subjected to directional freeze-forming and then dried to obtain a first intermediate. The first intermediate is pyrolyzed to obtain the second intermediate; The second intermediate is subjected to acid washing to form a graphene framework containing macropores and mesopores, wherein the pore size of the macropores is 400nm~600nm and the pore size of the mesopores is 40nm~60nm. Furthermore, a passivation layer comprising sequentially stacked amorphous Al2O3 layers and nanocrystalline TiN layers is prepared on the surface of the graphene framework.

5. The method for preparing conductive aerogel according to claim 4, characterized in that: It also satisfies at least one of the following conditions: (1) The macroporous sacrificial template includes at least one of PMMA microspheres, polystyrene microspheres, melamine-formaldehyde resin microspheres, polyethylene microspheres and polylactic acid microspheres; (2) The mesoporous inorganic template includes at least one of nano-CaCO3, nano-MgCO3, nano-ZnO, nano-MgO, nano-SiO2, NaCl and KCl; (3) The mass ratio between the macroporous sacrificial template and the mesoporous inorganic template is 1:(0.2~0.5); (4) The pyrolysis treatment includes: subjecting the first intermediate to a first pyrolysis treatment at a temperature of 400°C to 450°C, and then subjecting it to a second pyrolysis treatment at a temperature of 800°C to 900°C to obtain the second intermediate; (5) The temperature of the directional cryogenic molding process is -35℃ to -25℃; (6) The freezing direction of the directional freeze-forming process is vertically upward; (7) The drying process meets the following conditions: freeze drying at -50℃ to -60℃ for 24h to 48h; (8) A passivation layer comprising an amorphous Al2O3 layer and a nanocrystalline TiN layer is prepared on the surface of the graphene framework, satisfying the following conditions: the amorphous Al2O3 layer and the nanocrystalline TiN layer are prepared by atomic layer deposition, wherein the amorphous Al2O3 layer is grown for 50 to 60 cycles, with a thickness of 0.016 nm to 0.020 nm per cycle, a TMA pulse time of 0.015 s to 0.020 s, and an H2O pulse time of 0. The nitrogen purging time is 8s~12s, and the deposition temperature is 180℃~220℃; the nanocrystalline TiN layer is grown for 15~25 cycles, with a thickness of 0.020nm~0.030nm per cycle, a TiCl4 pulse time of 0.05s~0.06s, an NH3 pulse time of 0.10s~0.12s, a nitrogen purging time of 10s~15s, and a deposition temperature of 350℃~400℃; (9) The nanocrystalline TiN layer is prepared under the following conditions: TiCl4 is introduced with a pulse time of 0.05s to 0.06s; NH3 is introduced with a pulse time of 0.1s to 0.12s; the thickness of the nanocrystalline TiN layer is controlled to be 0.4nm to 0.6nm; and the grain size of the nanocrystalline TiN layer is 2nm to 3nm.

6. A positive electrode sheet, characterized in that, It includes a layered oxide active material, a conductive agent, and a binder, wherein the conductive agent is at least one of the conductive aerogels according to any one of claims 1 to 3 and the conductive aerogels prepared by the preparation method according to any one of claims 4 to 5.

7. The positive electrode sheet according to claim 6, characterized in that, The active substance is NaNi x Mn y Co z O2, where x+y+z=1, x≥0.

5.

8. A secondary battery, characterized in that, Includes the positive electrode sheet as described in any one of claims 6 to 7; Optionally, the secondary battery includes a sodium-ion battery; Further optionally, the sodium-ion battery also includes a negative electrode, a separator, and an electrolyte, wherein the electrolyte includes an aqueous electrolyte with a pH value of 7 to 14.

9. An electrochemical energy storage device, characterized in that, The invention includes at least one of the conductive aerogel according to any one of claims 1 to 3, the conductive aerogel prepared by the preparation method according to any one of claims 4 to 5, and the secondary battery according to claim 8, wherein the secondary battery is used to store electrical energy.

10. An electrical appliance, characterized in that, The invention includes at least one of the conductive aerogel according to any one of claims 1 to 3, the conductive aerogel prepared by the preparation method according to any one of claims 4 to 5, and the secondary battery according to claim 8, wherein the secondary battery is used to provide electrical energy.